Integrating ethnomathematics in E-LKPD: Enhancing learning through rice farming activities - Azizah, Annisa Nur; Rohmah, Mushlihah; Tyas, Wening; Sundawa, Denix Aricho (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Ethnomathematics offers valuable insights into how cultural practices can enrich mathematical understanding. This study focuses on integrating ethnomathematics related to rice farming activities into electronic Learning Module (E-LKPD) for enhancing mathematical education.Aim: The research aims to describe the developmental process and assess the effectiveness of the E-LKPD, which incorporates ethnomathematics content from rice farmer activities in paddy fields, in improving students' problem-solving abilities.Method: Employing the 4-D development model (Define, Design, Develop, and Disseminate), this research was conducted with eighth-grade students of SMP Al-Falah Nusaraya as subjects. Data were collected through observation, interviews, questionnaires, and tests on problem-solving abilities. Both descriptive statistics and t-test analyses were utilized to evaluate the data.Results: The study reveals that the E-LKPD is validated as effective by experts, with initial field trials placing it in the 'very practical' category. Moreover, results from field tests indicate that students using the E-LKPD with ethnomathematics content demonstrated superior problem-solving skills compared to those who did not use the E-LKPD.Conclusion: The E-LKPD containing ethnomathematics on rice farming activities significantly enhances students' problem-solving abilities, thereby validating the effectiveness of integrating cultural elements into mathematical education through innovative learning modules.